2017
DOI: 10.4172/2155-6156.1000760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Natal Catch-Down and Feeding Practices on Auxology, Body Composition and Muscle Function in Children Born Large-For-Gestational-Age

Abstract: Background: High birth-weight and supernormal postnatal weight gain increases the risk of obesity. Breastfeeding and postnatal Catch-down growth in children born large-for-gestational-age (LGA) might be protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…This observation was reinforced by the finding that the combined effect of increases in BW and age led to a BMI increase in 30.7% of study subjects. This finding was in agreement with other research findings [ 9 , 11 , 12 , 14 , 38 , 39 ]. In their study, Hill et al, found a positive correlation between BMI and BW for GA in adolescents diagnosed with obesity [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation was reinforced by the finding that the combined effect of increases in BW and age led to a BMI increase in 30.7% of study subjects. This finding was in agreement with other research findings [ 9 , 11 , 12 , 14 , 38 , 39 ]. In their study, Hill et al, found a positive correlation between BMI and BW for GA in adolescents diagnosed with obesity [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, some evidence shows that LGA babies are more likely to be overweight regardless of catch-down growth [ 10 ]. Consequently, being born LGA represents a considerable cardiovascular and metabolic risk [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the catch-down could not achieve complete normalization. 17 This is in line with our results, in which complete catch-down growth did not occur. Those with macrosomia remained within their growth percentile until 72 months of age.…”
Section: Discussionsupporting
confidence: 92%
“… 15 In a longitudinal growth study of 2,465 Chinese children, catch-down growth in weight, length, and ponderal index of high birth weight term infants was not achieved within 12 months of age. 16 Peters et al 17 showed in their study with LGA-children of mothers without GDM that 88% showed catch-down growth within 12 months of age. Despite the catch-down growth, the differences in the mean weight, length, and HC remained until 4 years of age, and those without catch-down growth had more subcutaneous fat.…”
Section: Discussionmentioning
confidence: 97%
“…Maternal influence in utero may be compensated by patterns of “catch-up” and “catch-down” growth for low birthweight and high birthweight infants respectively [ 54 ]. While the proportion and timing remains unclear, the “catch-down” growth phase has shown protective effects on body composition in 8-year-old children exposed to excess intrauterine fetal growth [ 55 ]. Despite this, an estimated 20% of high birthweight infants who do not enter “catch-down” growth represent a high-risk subgroup and maintain higher subcutaneous fat and BMI in later childhood [ 53 ].…”
Section: Discussionmentioning
confidence: 99%